« Douces choses férocement lointaines » : deux lectures de Proust dans les camps soviétiques - Guillaume Perrier (Amnis)
How is it possible to explain that Marcel Proust’s work raised the interest of a Polish painter and Russian writer, as they were struggling for life in soviet camps ? To answer this question, one should compare Joseph Czapski’s and Varlam Shalamov’s experiences : although these two authors didn’t know each other, Proust’s book represented for both of them, to some extent, a tool of resistance against the Soviet power, which was aiming their psychological and moral annihilation. Reading Proust against degradation (Czapski) and Kolyma Tales (Shalamov), several points of comparison appear : a same refusal of “committed literature”, a paradoxical connection between the camp’s environment and the Proustian world, a certain way of reading without book and, eventually, an exploration of consciousness in front of death.